Assessing Step Count–Dependent Changes in Femoral Articular Cartilage Using Ultrasound. (25th November 2019) - Pfeiffer, Steven J.; Davis‐Wilson, Hope C.; Pexa, Brett; Szymczak, Jessica; Wistreich, Catherine; Sorensen, Rachel; Wikstrom, Erik A.; Blackburn, J. Troy; Pietrosimone, Brian
Abstract : Objectives: To evaluate changes in the femoral cartilage cross‐sectional area (CSA) measured with ultrasound (US) between baseline and 1000, 2000, 3000, 4000, and 5000 steps of walking on a treadmill. Methods: Forty‐one healthy individuals completed a single testing session. Participants rested with their knees extended on a plinth for 45 minutes to unload the femoral cartilage. Ultrasound was used to acquire images of the femoral cartilage before the treadmill‐walking protocol. After the baseline US acquisition, participants walked on a treadmill at their preferred overground walking speed for 1000 steps, after which additional US images of the femoral cartilage were acquired. This process was repeated after 2000, 3000, 4000, and 5000 steps. A 1‐way repeated‐measures analysis of variance compared the CSA across the 6 step counts. An analysis of variance with repeated measures on time and Bonferroni corrected planned comparisons (.05/5) were used to evaluate differences in the femoral cartilage at each step count compared to baseline. Results: The study included 20 male and 21 female participants (mean age ± SD, 21.5 ± 2.8 years; mean body mass index, 24.3 ± 3.4 kg/m 2 ). The CSAs were significantly greater at the 2000‐step (1.27 ± 1.75 mm 2 ; P  < .001), 4000‐step (0.89 ± 1.17 mm 2 ; P  < .001), and 5000‐step (2.10 ± 1.73 mm 2 ; P  < .001) points compared to baseline. The CSA was significantly less at the 3000‐step point (1.05 ± 1.29 mm 2 ; P  < .001) compared to baseline. Conclusions: Changes in the CSA after walking may be dependent on the number of steps. The participants had a significant decrease in the CSA after 3000 steps of normal walking and a significant increase in the CSA after 2000, 4000, and 5000 steps of normal walking.